Refining student's creative thinking through problem oriented project-based learning and student team achievement division. (April 2020) - Supratman; Zubaidah, S; Corebima, AD; Ibrohim
Abstract: One of the biggest calls for educators to take part in the 21 st century learning is to make sure students equipped with creative thinking. To empower these skills, a variety of effective learning models can be implemented. The current study aimed to develop a learning model that has the potential to improve student creative thinking by integrating Problem-Oriented Project-Based Learning (POPBL) and Student Team Achievement Division (STAD), hence called POPBLSTAD. Plomp design was used as the procedures for developing this product. It consisted of preliminary investigation, design, realization/construction, test, evaluation, and revision. The model was examined through a quasi-experiment. The participants' creative thinking was evaluated based on five indicators: fluency, originality, elaboration, flexibility, and metaphorical thinking, using an essay test. The POPBLSTAD learning model was confirmed valid with a score of 3.47. The results of the ANACOVA analysis showed that the implementation of POPBLSTAD improved student creative thinking significantly. This finding suggests that POPBLSTAD can be used as an alternative learning model that is effective to refine student creative thinking.